2020
DOI: 10.1101/2020.05.17.100289
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of an African green monkey model for COVID-19

Abstract: 12Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for an unprecedented global 13 pandemic of COVID-19. Animal models are urgently needed to study the pathogenesis of COVID-19 and to 14 screen candidate vaccines and treatments. Nonhuman primates (NHP) are considered the gold standard model 15 for many infectious pathogens as they usually best reflect the human condition. Here, we show that African green 16 monkeys support a high level of SARS-CoV-2 replication and develop pronounced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
98
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(121 citation statements)
references
References 30 publications
18
98
2
3
Order By: Relevance
“…BAL uid collection was performed on days -8, 3, and 5 for all animals, as well as 7 dpi for AGM-4, AGM-5 and AGM-6. Consistent with our previous report describing the development of the combined intranasal and intratracheal SARS-CoV-2 challenge model in AGMs [10], we did not observe overt signs of clinical illness in any AGMs in this study, other than decreased appetite or brief (single day) anorexia (Supp Table 1). Temperature was longitudinally monitored in 15 minute increments for the entire study duration using surgically implanted temperature loggers; several animals (AGM-4, AGM-6) experienced brief (< 2 hours) periods of mildly elevated temperatures at 3 dpi, and two animals (AGM-2, AGM-3) exhibited an abnormal temperature cycling pattern at 3 dpi (Supp Figure 1).…”
Section: Sars-cov-2 Experimental Infection Of African Green Monkeys Usupporting
confidence: 93%
See 3 more Smart Citations
“…BAL uid collection was performed on days -8, 3, and 5 for all animals, as well as 7 dpi for AGM-4, AGM-5 and AGM-6. Consistent with our previous report describing the development of the combined intranasal and intratracheal SARS-CoV-2 challenge model in AGMs [10], we did not observe overt signs of clinical illness in any AGMs in this study, other than decreased appetite or brief (single day) anorexia (Supp Table 1). Temperature was longitudinally monitored in 15 minute increments for the entire study duration using surgically implanted temperature loggers; several animals (AGM-4, AGM-6) experienced brief (< 2 hours) periods of mildly elevated temperatures at 3 dpi, and two animals (AGM-2, AGM-3) exhibited an abnormal temperature cycling pattern at 3 dpi (Supp Figure 1).…”
Section: Sars-cov-2 Experimental Infection Of African Green Monkeys Usupporting
confidence: 93%
“…however, mild to moderate prolongation of the activated partial thromboplastin time (aPTT) was also observed in all animals through the acute phase of disease, most prominently in AGM-1 and AGM-2, indicating possible disorder of the intrinsic coagulation pathway ( Figure 1H, I); this was mirrored by increased levels of circulating brinogen ( Figure 1J). We previously showed that the pathways connected to IL-6 production are activated during SARS-CoV-2 infection of AGMs [10], indicating possible mechanisms of coagulopathy in the current study.…”
Section: All Animals Exhibited Normal Prothrombin Times (Pt) As Compasupporting
confidence: 64%
See 2 more Smart Citations
“…Although primarily a respiratory tract infection, extra-respiratory replication of SARS-CoV-2 has been observed in kidney, heart, liver and brain in fatal cases (7)(8)(9). Several experimental animal models for SARS-CoV-2 infection have been developed, including hamsters (10) ferrets (11) and non-human primate models (12)(13)(14)(15). SARS-CoV-2 pathogenicity within these animal models ranges only from mild to moderate (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%